Is Man the Measure of All Things? A Social Cognitive Account of Androcentrism. (November 2019) - Bailey, April H.; LaFrance, Marianne; Dovidio, John F.
Androcentrism refers to the propensity to center society around men and men's needs, priorities, and values and to relegate women to the periphery. Androcentrism also positions men as the gender-neutral standard while marking women as gender-specific. Examples of androcentrism include the use of male terms (e.g., he ), images, and research participants to represent everyone. Androcentrism has been shown to have serious consequences. For example, women's health has been adversely affected by over-generalized medical research based solely on male participants. Nonetheless, relatively little is known about androcentrism's proximate psychological causes. In the present review, we propose a social cognitive perspective arguing that both social power and categorization processes are integral to understanding androcentrism. We present and evaluate three possible pathways to androcentrism deriving from (a) men being more frequently instantiated than women, (b) masculinity being more "ideal" than femininity, and/or (c) masculinity being more common than femininity.